2019
DOI: 10.1111/1365-2745.13316
|View full text |Cite
|
Sign up to set email alerts
|

Predicting species abundances in a grassland biodiversity experiment: Trade‐offs between model complexity and generality

Abstract: Models of natural processes necessarily sacrifice some realism for the sake of tractability. Detailed, parameter‐rich models often provide accurate estimates of system behaviour but can be data‐hungry and difficult to operationalize. Moreover, complexity increases the danger of ‘over‐fitting’, which leads to poor performance when models are applied to novel conditions. This challenge is typically described in terms of a trade‐off between bias and variance (i.e. low accuracy vs. low precision). In studies of ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Goodness‐of‐fit is a useful diagnostic, but it cannot be used to select predictive models from a set of candidates since the fit of a model always increases with the addition of covariates (although this may be moderately accounted for by using an adjusted R 2 ). Information criteria (e.g., AIC, BIC, DIC) are statistical tools useful for correcting goodness‐of‐fit by including a term that penalizes increases in model complexity (as measured by the number of parameters and sample size; Burnham and Anderson 2002, Clark et al 2020). The standard model selection framework using information criteria involves fitting competing models to the same data and then assessing these models with information criteria to determine the most parsimonious model.…”
Section: Introductionmentioning
confidence: 99%
“…Goodness‐of‐fit is a useful diagnostic, but it cannot be used to select predictive models from a set of candidates since the fit of a model always increases with the addition of covariates (although this may be moderately accounted for by using an adjusted R 2 ). Information criteria (e.g., AIC, BIC, DIC) are statistical tools useful for correcting goodness‐of‐fit by including a term that penalizes increases in model complexity (as measured by the number of parameters and sample size; Burnham and Anderson 2002, Clark et al 2020). The standard model selection framework using information criteria involves fitting competing models to the same data and then assessing these models with information criteria to determine the most parsimonious model.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in understanding how species interactions within ecological communities modulate coexistence as well as community diversity and stability, has driven a reassessment of the assumptions and simplifications commonly made in individual fitness modeling. Clark et al (2019) found that too much added information can degrade the accuracy of fitness models, but also found that the best models are not the simplest models that are commonly used. Though higher-order interactions are widely recognized to be an important group of interactions in natural communities, the issues they cause in modeling individual fitness are not trivial and have driven the opinion that the value of HOIs is not sufficient to merit the issues they cause with modeling (Levine et al, 2017); a conclusion we feel is premature.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a recent paper by Clark et al (2019) found that models of intermediate complexity are the best at predicting local patterns of diversity. Clark et al's (2019) careful comparison of models containing different amounts of information made an important point: there is often a trade-off between how much biological information we include in models and their accuracy. It remains unclear, however, which biological details (rather than just how many) are the most important for accurately modeling and predicting coexistence outcomes and patterns of diversity.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in answering this question resides in knowing the exact equations governing the dynamics of ecological systems, together with the high uncertainty regarding the initial conditions, parameter values, intrinsic randomness, and more importantly, how the changing external conditions (such as biotic and abiotic factors) will affect the dynamics (Levins, 1968; Sugihara, 1994; Fukami, 2015; Boettiger, 2018; Cenci and Saavedra, 2018b). This complexity of multidimensional and changing factors has typically taken both theoretical and empirical studies to choose between understanding and predicting species persistence (Petchey et al ., 2015; Clark et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, biodiversity forecasting spans and integrates many model‐driven (parametric) and data‐driven (nonparametric) methodologies, such as uncertainty propagation, statistics, informatics, Bayesian approaches, machine learning, Markov chain approaches, empirical dynamic modelling (Sugihara et al ., 2012; Harfoot et al ., 2014; Cazelles et al ., 2016; Dietze, 2017; Cenci and Saavedra, 2019; Adams et al ., 2020; Maynard et al ., 2020), as well as parameterising complex mechanistic models using either demographic, eco‐physiological or allometric information (Preston, 1962; Pacala et al ., 1996; Dietze, 2017). However, the majority of these methodologies demands extensive amounts of data, their explanatory power has been contested, and their generalisation has not always been validated with experimental work (Dietze, 2017; Clark et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%